Adherence to recommendations for early repeat cervical smear tests. Issue 6688 (17th June 1989) - Mitchell, H.; Medley, G.
Abstract : OBJECTIVE--To assess adherence to recommendations for an early repeat cervical smear test in women with reports of cytological abnormalities, and to evaluate the impact of reminder letters to medical practitioners when such smear tests are overdue. DESIGN--Observational study. SETTING--Cytology (gynaecological) service for Victoria, Australia. SUBJECTS--Two groups of women who had abnormal cervical smears during 1985. Women in group A had some evidence of an important dysplasia and were advised to have a repeat smear in three months' time whereas women in group B had a less serious abnormality and were advised to have a repeat smear test in six months' time. In all, 971 of the 1036 women in group A and 1401 of the 1464 women in group B were eligible to have a repeat smear analysed by the service. INTERVENTION--If a repeat smear had not been received within three months of the recommended date a reminder letter generated by the service's computer was sent to the medical practitioner who had taken the smear. END POINT--Thirty six months after the report on the abnormal smear was issued. MEASUREMENTS AND MAIN RESULTS--In all, 870 (90%) of the women in group A and 1154 (82%) of the women in group B had a repeat smear test. The mean time to a repeat test was 3.0 months (95% confidence interval 0.5 to 16.4) in group A and 6.0 months (1.2 to 30.3) in group B. The reminder letter to the practitioner potentially increased the rate of return for a repeat smear test by 18% in group A and 24% in group B. Adherence to the recommendation for a repeat test increased with increasing age. CONCLUSIONS--Achieving high rates of follow up smear tests and appropriate management in women with cytological abnormalities is critical to the impact of a screening programme for cervical cancer. The reminder system used in this study was not labour intensive or expensive and provided a fail safe mechanism for ensuring that reports of abnormal smears were not overlooked.